Association of Social Media Use With Social Well-Being, Positive Mental Health, and Self-Rated Health: Disentangling Routine Use From Emotional Connection to Use. (December 2019) - Bekalu, Mesfin A.; McCloud, Rachel F.; Viswanath, K.
Most studies addressing social media use as a normal social behavior with positive or negative effects on health-related outcomes have conceptualized and measured social media use and its effects in terms of dose–effect relations. These studies focus on measuring frequency and duration of use, and have seldom considered users' emotional connections to social media use and the effects associated with such connections. By using a scale with two dimensions capturing users' integration of social media use into their social routines and their emotional connection to the sites' use, the present study has brought preliminary evidence that may help map where social media use, as a normal social behavior, may be considered beneficial or harmful. Data from a nationally representative sample ( n = 1, 027) of American adults showed that while routine use is associated with positive health outcomes, emotional connection to social media use is associated with negative health outcomes. These associations have been consistent across three health-related outcomes: social well-being, positive mental health, and self-rated health. The data also showed that the strength of the positive and negative associations of routine use and emotional connection with the health outcomes varies across socioeconomic and racial/ethnic population subgroups. Our findings suggest that the link between social media use and health may not only be captured by and explained in terms of conventional dose–effect approaches but may also require a more sophisticated conceptualization and measurement of the social media use behavior.